Once an entrepreneur, always an entrepreneur? The impacts of skills developed before, during and after college on firm start-ups - Peter F. Orazem; Robert Jolly; Li Yu (IZA Journal of Labor Economics, 2015)
By allowing agents to switch from entrepreneurship to wage work and vice versa over the life cycle, this study proposes a dynamic Jacks-of-All-Trades (JAT) model where entrepreneurs invest in highly varied skills to manage their business. We simultaneously endogenize human capital investment and occupational decisions. Using the survey data of Iowa State alumni graduating between 1982 and 2006, we find that the probability of selecting a broad curriculum, having a more varied career, and becoming an entrepreneur are jointly positively correlated. Academic diversity is found to be initially important in starting a business shortly after completing schooling, but its importance declines over time.
Keywords: J24; 330; Entrepreneurship; Jacks-of-all-trades; Educational experiences; Working experience; Entry